2011
DOI: 10.1007/s11269-011-9945-4
|View full text |Cite
|
Sign up to set email alerts
|

Sediment Yield Assessment of a Large Basin using PSIAC Approach in GIS Environment

Abstract: Reservoirs are the key infrastructure for the socio-economic development of a country. The reservoirs are proven to be a remedial solution of highly erratic spatial and temporal availability of water. The growth in population and consequent developmental activities within a catchment area has shown to aggravate the problem of sedimentation which comprised of erosion, sediment transport and its deposition in these reservoirs. Among all above mentioned, reservoir sediment deposition is most important as it reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This could be related to the reason that the study catchment could be characterized by very low soil infiltration, low soil water holding capacity and poor vegetation cover (inappropriate land use system), and low conservation measures. Consistent with this finding and explanation many previous reports indicated that a higher soil loss rate is strongly associated with high runoff resulting from absence of runoff flow obstacles such as vegetation cover, conservation measures, impoundments, and soil with low infiltration rate and low soil water holding capacity [54][55][56][57][58][59][60]. If an average annual soil generation rate of 6 t ha −1 y −1 [61] is considered, the soil loss rates estimated by the model in most parts of the catchment could be beyond this acceptable level.…”
Section: Mmf Model Evaluation In Relation To Other Studies (Models)supporting
confidence: 91%
“…This could be related to the reason that the study catchment could be characterized by very low soil infiltration, low soil water holding capacity and poor vegetation cover (inappropriate land use system), and low conservation measures. Consistent with this finding and explanation many previous reports indicated that a higher soil loss rate is strongly associated with high runoff resulting from absence of runoff flow obstacles such as vegetation cover, conservation measures, impoundments, and soil with low infiltration rate and low soil water holding capacity [54][55][56][57][58][59][60]. If an average annual soil generation rate of 6 t ha −1 y −1 [61] is considered, the soil loss rates estimated by the model in most parts of the catchment could be beyond this acceptable level.…”
Section: Mmf Model Evaluation In Relation To Other Studies (Models)supporting
confidence: 91%
“…In this study, we used the Revised Universal Soil Loss Equation (RUSLE) model (Renard et al, 1997) to estimate soil loss and map its spatial variability. This model has been selected because it requires minimal data and has a low computational cost, rendering it more suitable for data scarce regions (Garg and Jothiprakash, 2012;Chowdary et al, 2013). In addition, some of the key model parameters have been calibrated for Ethiopian conditions (e.g., Hurni, 1985).…”
Section: Model Selection and Parameterizationmentioning
confidence: 99%
“…For areas where quality data for model building and calibration are scarce, empirical models such as the RUSLE may give better approximation of soil loss (Renard et al 1997) compared to complex physical based models that require detailed data (Garg and Jothiprakash 2012;Chowdary et al 2013). Accordingly, the RUSLE adjusted for SDR is used in this study to assess soil erosion risk with a spatial resolution of 250 m at regional scale.…”
Section: Parameterization Of the Rusle Modelmentioning
confidence: 99%